Rencana Pengembangan Tata Ruang Dan Infrastruktur Dasar Desa Pulau Telo - Roland Kurniawan; Andreas Miriadi; Muhammad Wisnu Reksa Kadarma; Vanessa Kahayanti Subroto; Baginda Syahdeva Hasibuan; Rima Ratna Dewanti; Bima Agung Saputra; Tomas Leonardo (Fakultas Teknik Universitas Palangka Raya, 2025)
Spatial planning and basic infrastructure are major challenges in Pulau Telo Village, Kapuas Regency, which faces issues of overlapping land functions and flood risks due to low-lying geographical conditions. This community service aims to develop technical recommendations for adaptive village infrastructure development based on local aspirations. The implementation method uses a participatory-technical approach through field observations, community discussions, and engineering designs using AutoCAD, SketchUp, and Revit software. The results of the service are in the form of Detailed Engineering Design (DED) documents and Budget Plans (RAB) for four priority infrastructures: a 960 m² Village Market with flood elevation mitigation, a Waste Bank system (1 distribution building and 7 posts), a Village Gate, and 7 RT Boundary units. The total estimated planned budget is Rp2.001.927.274,00. This document serves as a strategic reference for the village government in submitting funding and integration into the Village Medium-Term Development Plan (RPJMDes) to ensure measurable and sustainable development.